'Full of ugly sights, of ghastly dreams': Dreams and tragedy in Shakespeare's Richard III. (April 2017) - Fretz, Claude
This article argues that dreams are an important and deliberate part of Shakespeare's conception of tragedy in Richard III . Shakespeare, when composing this play, exploited the uncertainty in his time about whether dreams were natural or supernatural phenomena in order to deploy dream devices as a form of commentary on the material as well as spiritual implications of his characters' actions. As a result, dreams ultimately sharpen the play's focus on human agency by amplifying the characters' ambitions, crimes and guilty consciences.